Audit Fees in Malaysia: Does Corporate Governance Matter? - Effiezal Aswadi Abdul Wahab; Mazlina Mat Zain; Kieran James (Asian Academy of Management Journal of Accounting and Finance, 2011)
This study examines the relationship between corporate governance and audit fees during the period before and after the enactment of the Malaysian Code of Corporate Governance (MCCG). Our panel analysis of 379 firms during the 1999–2002 period reveals a significant and positive relationship between corporate governance and audit fees. However, the relationship becomes weaker after 2001, suggesting that the MCCG reduced firms' control and inherent risk, thus ultimately contributing to reduced audit effort in Malaysia. Our findings remain viable after we control for political connections unique to Malaysia's capital market.